School bag weight and the occurrence of back pain among elementary school children - Semuel Layuk; Tri Martiana; Bongakaraeng Bongakaraeng (SAGE Publishing, 2020)
Background: Children in primary schools use school bags to carry study material, although the heavy bags are often associated with musculoskeletal problems, especially back pain. This practice requires strength, which significantly changes the body posture and walking pattern, subsequently leading to the incidence of back pain as a side effect. The aim of this study, therefore, is to analyze the differences in bag loads between elementary school children in urban and suburban area, and also analyze the relationship with the occurrence of back pain. Design and methods: This was a cross sectional study, which used stratified random sampling to choose 2 elementary schools each representing the urban and suburban areas. Furthermore, a total sample of 164 students were selected, whose school bag weight were measured for 5 consecutive days, particularly in the morning on respondents arrival at school. Moreover, the occurrence of back pain was evaluated using a modified Nordic map, and data analysis required the use of independent sample analysis t test and χ2 test. Results: The results showed the presence of highly significant differences in the school bags weight of respondents in the urban and suburban areas, as well as between schools using the 2013 curriculum and otherwise. Conclusions: In conclusion, there is a correlation between the weight measured and the occurrence of back pain, hence the 2013 curriculum is recommended to be adopted by all elementary schools. Also, the use of lockers to store items used at school repeatedly by children is also highly encouraged.